2016
DOI: 10.1111/ejss.12401
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the soil water retention curve for structured soil from saturation to oven‐dryness

Abstract: The soil water retention curve (SWRC) is the most fundamental soil hydraulic function required for modelling soil–plant–atmospheric water flow and transport processes. The SWRC is intimately linked to the distribution of the size of pores, the composition of the solid phase and the soil specific surface area. Detailed measurement of the SWRC is impractical in many cases because of the excessively long equilibration times inherent to most standard methods, especially for fine textured soil. Consequently, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 37 publications
1
29
1
1
Order By: Relevance
“…A number of studies used a constant value at pF 0 ( W = 0, pF 0 ) of 6.7 to 7.1 (Ross et al, 1991; Rossi and Nimmo, 1994; Fayer and Simmons, 1995; Webb, 2000; Groenevelt and Grant, 2004; Schneider and Goss, 2012; Arthur et al, 2013). Since studies have shown that pF 0 can be variable depending on the clay mineralogy or cation exchange capacity (Lu and Khorshidi, 2015; Karup et al, 2017), we anchored the CS function instead at the gravimetric soil water content at −10 6 cm H 2 O ( W 6 , pF = 6). Consequently, the two parameters in the CS function became W 6 and α, and therefore, the modified CS function can be expressed as W=W6+α1(6pF)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies used a constant value at pF 0 ( W = 0, pF 0 ) of 6.7 to 7.1 (Ross et al, 1991; Rossi and Nimmo, 1994; Fayer and Simmons, 1995; Webb, 2000; Groenevelt and Grant, 2004; Schneider and Goss, 2012; Arthur et al, 2013). Since studies have shown that pF 0 can be variable depending on the clay mineralogy or cation exchange capacity (Lu and Khorshidi, 2015; Karup et al, 2017), we anchored the CS function instead at the gravimetric soil water content at −10 6 cm H 2 O ( W 6 , pF = 6). Consequently, the two parameters in the CS function became W 6 and α, and therefore, the modified CS function can be expressed as W=W6+α1(6pF)…”
Section: Methodsmentioning
confidence: 99%
“…During the last decades, many researchers have developed functions to predict the dry‐end SWRC using basic soil properties (e.g., clay content). Karup et al (2017) predicted the water content at −10 6 cm H 2 O (log 10 |−10 6 | = pF 6) using the clay content, organic matter, and silt fraction as well as the bulk density coupled with the assumption of linearity between pF 4.2 and pF 6.9. Schneider and Goss (2012), based on 18 samples, showed that the dry end of the SWRC can be successfully predicted from a PTF based on clay content.…”
mentioning
confidence: 99%
“…These contradictory results may be rooted in the uncertainties in water dynamics. Water dynamics and water retention curves can be obtained from arduous measurements (Várallyay és Rajkai 1987), pedotransfer functions (Rajkai and Kabos 1999;Makó et al 2010;Tóth et al 2015;Karup et al 2016;Gohardoust et al 2017) or numeric models, e.g. the RETention Curve computer program (RETC) (van Genuchten et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Processes such as roots shrinkage and exudation on drying have been characterised by imaging techniques or soil physical-chemical analyses [6][7][8][9][10] and are inducing counterposed effects on soil:…”
Section: Introductionmentioning
confidence: 99%